Major surgical trauma differentially affects T-cells and APC. Issue 1 (January 2015) - Albertsmeier, Markus; Quaiser, Dominik; von Dossow-Hanfstingl, Vera; Winter, Hauke; Faist, Eugen; Angele, Martin K
Macrophages have been reported to initiate immunosuppression following trauma and hemorrhage, and recent experimental studies suggest a pivotal role of T-cells in maintaining immunosuppression. The aim of the present study was to investigate the interaction of APC and T-cells in humans following major surgery. First, APC and T-cells from 14 surgical patients were isolated, counted and characterized by their specific surface marker profile 2 and 24 h postoperatively. Then, these cells were co-incubated with cells of the other type, which had been isolated pre-operatively. Chemokine secretion from pre-operative cells as measured by enzyme immunoassay served as a bioassay for the function of the stimulating postoperative cells. CD3 + T-cells and surface marker CD28 were markedly suppressed postoperatively, while CD3 + CD25 + CD127 − Treg s were not suppressed. CD14 + APC counts were increased with the most significant increase observed in CD14 + HLA-DR − myeloid-derived suppressor cells. In co-cultures, APC showed increased postoperative secretion of TNF-α and IL-6 independently of whether they had been co-incubated with pre- or postoperative T-cells. T-cells incubated with CD14 + cells 2 h postoperatively secreted diminished amounts of IFN-γ. The results of the study suggest that T-cells play a pivotal role in mediating immunosuppression after major abdominal surgery.